Ethnicity as a predictor of detention under the Mental Health Act. - Singh, S; Burns, T; Tyrer, P; Islam, Z; Parsons, H; Crawford, M (Cambridge University Press, 2014)
BACKGROUND: There has been major concern about the 'over-representation' of Black and ethnic minority groups amongst people detained under the Mental Health Act (MHA). We explored the effect of patient ethnicity on detention following an MHA assessment, once confounding variables were controlled for. METHOD: Prospective data were collected for all MHA assessments over 4-month periods in the years 2008, 2009, 2010 and 2011 each in three regions in England: Birmingham, West London and Oxfordshire. Logistic regression modelling was conducted to predict the outcome of MHA assessments - either resulting in 'detention' or 'no detention'. RESULTS: Of the 4423 MHA assessments, 2841 (66%) resulted in a detention. A diagnosis of psychosis, the presence of risk, female gender, level of social support and London as the site of assessment predicted detention under the MHA. Ethnicity was not an independent predictor of detention. CONCLUSIONS: There is no evidence for that amongst those assessed under the MHA, ethnicity has an independent effect on the odds of being detained.